Modelling and Numerical Studies of Discrete Dislocation Dynamics - Kolář, Miroslav; Beneš, Michal; Kratochvíl, Jan (Proceedings of the Conference Algoritmy, 2016)
We investigate a possible inaccuracy in discrete dislocation dynamics (DDD) simulations.  As a model problem we consider two distinct dislocations of the opposite signs, gliding and bowing out in  parallel slip planes in a channel of persistent slip band (PSB). Dislocations are pushed by the applied stress and when overlap, they either pass or form a dipole. The objective of our study is to determine  the lower and upper estimate of the passing stress needed to escape each other. In our simulations, we consider two loading regimes - the stress controlled and the total strain controlled regime. The motion law is described by  the mean curvature flow of planar curves and treated by the parametric method.  Results of our numerical experiments indicate that the upper and lower estimate of the passing stress differ less than 10%.